Análise espectrofotométrica da capacidade quelante do EDTA 17%, ácido cítrico 1% e ácido cítrico 10% - Lazaro, Leandro Lofgren. (2007)
From the current instrumentation methods employed in the endodontal therapy may result a residual organic and inorganic matter layer formation which might be able to retain bacteria and their by-products. Chemical etching, ultrasound and laser exertion are suitable alternatives for smear layer removal. None of these service options is absolute. There is no common sense regarding the effectiveness of such techniques. The effects of EDTA, 1% citric acid and 10% citric acid upon root dentin were assessed by a method which included the contact of powdered dentin with the beforehand mentioned substances within three different time lenghts: 1 minute, 3 minutes and 5 minutes. An evaluation under an inductively coupled plasma-optical emission spectrophotometer afterwards was achieved in order to rate the amount of chelated calcium.